Diagnostic value of elevated serum angiotensin-converting enzyme and lymphopenia in patients with granulomatous hepatitis - El Jammal, Thomas; Dhelft, François; Pradat, Pierre; Bailly, François; Zoulim, Fabien; Hot, Arnaud; Fauter, Maxime; Drissi-Bakhkhat, Ayoub; Durieu, Isabelle; Lega, Jean-Christophe; Jamilloux, Yvan; Sève, Pascal (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim : Granulomatous hepatitis (GH) is associated with various aetiologies, especially inflammatory and infectious disorders. Sarcoidosis is a granulomatous disease in which the liver is the fourth most affected organ. Since epithelioid cell granulomas are not specific to sarcoidosis and since most patients with hepatic sarcoidosis are asymptomatic, valuable diagnostic biomarkers are needed to support the diagnosis of sarcoidosis. This study proposes to assess the diagnostic value of serum angiotensin converting enzyme (sACE) and lymphopenia in GH for sarcoidosis. Methods : We retrospectively analyzed the records of 90 patients referred to the internal medicine or hepatogastroenterology departments of the Lyon University Hospital (Lyon, France) between March 2002 and January 2020 in a context of GH. Results : In our tertiary center, 38 patients with sarcoidosis were identified among 73 patients with GH. Lymphopenia had a high specificity (85.7%), which increased when combined with elevated (97.0%). Interestingly, specificity increased in patients under 50 years old (100%). Conclusions: Those results suggests that lymphopenia and sACE may be valuable biomarkers for sarcoidosis diagnosis in GH when combined, especially in younger patients.